RETRACTED: Environmental concern in the era of digital fiscal inclusion: The evolving role of human capital and ICT in China - Sohail, Muhammad Tayyab; Yang, Minghui (Frontiers in Psychology, 2022)
To achieve environmental sustainability, the role of human capital and financial inclusion has been debated in limited empirical studies. Employing a reliable ARDL model approach, this study examines the dynamic link between human capital and ICT, financial inclusion, and CO2 emissions using the China economy dataset over the period 1998–2020. The vivacious side of human capital shows that literacy rate and average year of schooling curb CO2 emissions in long run. The results of human capital are also based on facts in magnitude as well as in direction. Also, empirics unfold that digital financial inclusion significantly increases CO2 emissions. Based on these novel findings, a wide set of economic policies are repaired for environmental quality. Environmental education should be considered at early levels of education. The authorities and policymakers should fix energy-related issues through education. The China government should stimulate the educational sector to conduct a clean and green revolution that acts as a mechanism for a green and clean economy. This study's finding is more effective than the previous unlike empirical studies for policy-making due to the advanced econometric method.